The effect of visual feedback and shouting on the maximum muscle strength of the grip, quadriceps femoris and hamstring - Han, Sun-Gyu; Bae , So-Young; Han , Tae-Won; Kim , Jin-Seop; Yu , Jae-Ho; Lee, Dong- Yeop (International Journal of Psychosocial Rehabilitation, 2020)
Background/Objectives: The purpose of this study was to ensure that applying visual feedback and shouting at the same time during exercise is effective in improving the maximal strength. Methods/Statistical analysis: The visual feedback and shouting were applied randomly simultaneously to the basic movement of 30 healthy adults, and the grip strength was compared through repeated measurements, the knee muscles involved to the quadriceps femoris, and the femoral muscles applied to the hamstring. Findings: The grip strength was a slight muscle improvement in the group applying visual feedback over the experimental group and in the group applying shouting over the experimental group, the right knee extension quadriceps femoris was a significant improvement in the group applying visual feedback (p<.01) and the left knee extension quadriceps femoris was enhancement in the group involving visual feedback over the experimental group (p<.01). The right knee flexion of hamstring was a significant improvement in the group comprising visual feedback (p<.01), and the left knee flexion of hamstring was an enhancement in the group applying visual feedback over the experimental group (p<.01). Improvements/Applications: The results of the study showed that the group improved the maximum muscle strength of the quadriceps femoris and hamstring muscles in the lower extremities with visual feedback and shouting. Furthermore, comparing maximum muscle strength with visual feedback and shouting has shown that shouting is more significant.